The Reformation of Cathedrals : Cathedrals in English Society - Lehmberg, Stanford E. (Book collections on Project MUSE., 1988)
Stanford Lehmberg, a noted authority on the Tudor period, examines the impact of the Reformation on the cathedrals of England and Wales. Based largely on manuscript materials from the cathedral archives themselves, this book is the first attempt to draw together information for all twenty-nine of the cathedrals that existed in the Tudor period. The author scrutinizes the major changes that took place during this era in the institutional structure, personnel, endowments, liturgy, and music of the cathedral and shows how the cathedrals, unlike the monasteries that were dissolved by Henry VIII, succeeded in adapting successfully to the Reformation. Forty-two illustrations depict sixteenth-century changes in cathedral buildings.Narrative chapters trace the changes that occurred during the reigns of Henry VIII, Edward VI, "Bloody" Mary, and Elizabeth I. Analytical sections are devoted to cathedral finance and cathedral music. The changing lives of cathedral musicians are described in some detail, and even greater attention is paid to the cathedral clergy, whose living conditions changed markedly when they were allowed to marry. Using a variety of sources, including such physical remains as tombs and monuments, the concluding chapter discusses the role of cathedrals in English society.Originally published in 1989.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.